Impact of Drought Stress on Peanut (Arachis hypogaea L.) Productivity and Food Safety - Kambiranda, Devaiah M.; Vasanthaiah, Hemanth KN.; Ananga, Ramesh Katam Athony; Basha, Sheikh M.; Naik, Karamthotsivasankar (IntechOpen, 2011)
None